2002
DOI: 10.1103/physrevb.66.075115
|View full text |Cite
|
Sign up to set email alerts
|

Surface and curvature energies from jellium spheres: Density functional hierarchy and quantum Monte Carlo

Abstract: We consider spherical jellium clusters with up to 200 electrons as a testing ground for density functional approximations to the exchange-correlation energy of a many-electron ground state. As nearly-exact standards, we employ Hartree-Fock energies at the exchange-only level and the diffusion Monte Carlo ͑DMC͒ energies of Sottile and Ballone ͑2001͒ at the correlated level. The density functionals tested are the local spin density ͑LSD͒, generalized gradient ͑GGA͒, and meta-generalized gradient ͑meta-GGA͒ appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 37 publications
5
38
1
Order By: Relevance
“…Usually GGA works better than LDA, but not for the jellium surface energy where long-range effects are especially important. In the present work, as in four others, 10,31,34,35 we have found that the jellium xc surface energy is only a few percent higher than it is in LDA. These closely-agreeing methods include two different short-range corrections to RPA (present work using a non-local xc kernel and Ref.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Usually GGA works better than LDA, but not for the jellium surface energy where long-range effects are especially important. In the present work, as in four others, 10,31,34,35 we have found that the jellium xc surface energy is only a few percent higher than it is in LDA. These closely-agreeing methods include two different short-range corrections to RPA (present work using a non-local xc kernel and Ref.…”
Section: Discussionsupporting
confidence: 84%
“…10), extraction of a surface energy from DMC energies for jellium spheres (Ref. 34), and a meta-GGA density functional (Ref. 7).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GGA-PBE surface energies are generally lower [14]. This paradox has been discussed by Almeida et al [15]. Meta-GGA-PKZB has been employed to improve the GGA surface energy of the jellium model [14].…”
Section: Introductionmentioning
confidence: 99%
“…These results have been later compared against several DFT approximations 19,20 . Surface correlation energies 18 and surface exchange-correlation energies 19,20 have been obtained using extrapolated values to infinite size.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…These results have been later compared against several DFT approximations 19,20 . Surface correlation energies 18 and surface exchange-correlation energies 19,20 have been obtained using extrapolated values to infinite size. In general, the values obtained for correlation surface energies obtained with spheres are consistent with the latest DMC results for jellium slabs 21 and other methods, but differ to some extent from the original DMC results from slab geometries 22 .…”
Section: Pacs Numbersmentioning
confidence: 99%